Nickel ion release from dental alloys in two different mouthwashes - Karim Jafari; Saeed Rahimzadeh; Somayeh Hekmatfar (Tabriz University of Medical Sciences, 2019)
Background. Mouthwashes are widely used as adjuncts to mechanical oral hygiene procedures. Nonetheless, there is little information regarding the effect of various mouthwashes on the amount of ions released from the nickel-chromium (Ni‒Cr) alloys used in the fabrication of fixed prostheses. Therefore, the present study was conducted to evaluate the effect of two types of mouthwash on the release of Ni ions from dental alloys. Methods. Forty-two disk-shaped specimens were prepared with a diameter of 10 mm and a height of 2 mm. Two mouthwashes were examined in this study: Oral B and Listerine. A control group was also considered using distilled water. Each Ni‒Cr disk was immersed in the mouthwashes and distilled water in polypropylene test tubes, and then incubated at 37°C to simulate the oral temperature. After 45 days of incubation, the samples were tested for Ni ions using inductively coupled plasma mass spectroscopy. Data were analyzed using ANOVA. Results. In the Halita group subjects exhibited 2.04±0.65 reduction in OLS. OLS reduction in the chlorhexidine group was 1.95±0.74. Statistical analysis showed no significant difference between the two groups (P>0.05). Conclusion. As the results indicated, the amount of ion release was within the safe limits in the two experimental groups. However, it is recommended that prescribe Listerine mouthwash should not be prescribed for the patients with a history of Ni allergy.